Behavior Change Communication as a Strategy to Educate Parents in Guiding Children to Successful Online Learning - Dwi Agustina; Mohammad Raudy Gathmyr; Md.Ahsan Habib; Pattarapohn Tangphutthiuransakul (Yayasan Ilomata, 2022)
Since before the outbreak of the corona virus, parents have an obligation to support their children's education in schools. The implementation of online learning as an effort to prevent the spread and transmission of this virus has made the role of parents even greater in the education of their children. The research is aimed at finding out how the behavior change communication program carried out by the government is implemented and what obstacles parents encounter in assisting their children to study at home. This is a qualitative research with a phenomenological approach. The phenomenological approach was chosen because the researchers wanted to dig deeper into the experiences of the informants, especially related to assisting children in online learning. Data was collected by semi-structured interviews with 20 informants consisting of parents of students in grades 1 to 3 of elementary schools in Jakarta. The results of this study indicate that behavioral change communication carried out in order to change the behavior of parents so that they want to accompany their children to study from home is quite successful after going through the pre-contemplation, contemplation, preparation, action and maintenance stages.